2008
DOI: 10.1097/hjh.0b013e3282f52c36
|View full text |Cite
|
Sign up to set email alerts
|

Effects of telmisartan, a unique angiotensin receptor blocker with selective peroxisome proliferator-activated receptor-γ-modulating activity, on nitric oxide bioavailability and atherosclerotic change

Abstract: In addition to a class effect of ARBs, telmisartan may have additional effects on nitric oxide bioavailability and atherosclerotic change through its PPAR gamma-mediated effects in genetically hyperlipidemic rabbits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 26 publications
6
33
0
Order By: Relevance
“…Interestingly, PPAR-γ has a protective role in vascular function and structure via anti-inflammatory, anti-fibrotic, and antioxidant actions (35,36). Recent studies have shown that telmisartan has an ameliorative effect on endothelial dysfunction by improving the PPAR-γ-eNOS system in Dahl salt-sensitive hypertensive rats (37) or NO bioavailability in Watanabe heritable hyperlipidemic rabbits (38). Thus, in addition to effects on the response to NO in vascular smooth muscle cells, improvement of endothelial dysfunction might, in part, participate in the beneficial effects of telmisartan on NO-mediated vasorelaxation dysfunction in SHR-cp.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, PPAR-γ has a protective role in vascular function and structure via anti-inflammatory, anti-fibrotic, and antioxidant actions (35,36). Recent studies have shown that telmisartan has an ameliorative effect on endothelial dysfunction by improving the PPAR-γ-eNOS system in Dahl salt-sensitive hypertensive rats (37) or NO bioavailability in Watanabe heritable hyperlipidemic rabbits (38). Thus, in addition to effects on the response to NO in vascular smooth muscle cells, improvement of endothelial dysfunction might, in part, participate in the beneficial effects of telmisartan on NO-mediated vasorelaxation dysfunction in SHR-cp.…”
Section: Discussionmentioning
confidence: 99%
“…At the in vivo level, GW9662-sensitive telmisartan effects include the inhibition of choroidal neovascularization in mice (Nagai et al, 2006), the improvement of endothelial NO release and reduction of atherosclerotic plaques in Watanabe hyperlipidemic rabbits (poorly mimicked by candesartan) (Ikejima et al, 2008), the restoration of endothelial NO synthase and PPAR-g 826 expression in Dahl salt-sensitive rats (Kobayashi et al, 2008b), the improvement of vascular dysfunction in subtotally nephrectomized rats (partly mimicked by losartan) (Toba et al, 2012), and the prevention of hydronephrosis after unilateral ureteral obstruction in AT1R knockout mice (partly mimicked by losartan) (Kusunoki et al, 2012). Metabolic parameters affected by telmisartan in a GW9662-sensitive manner include fatty acid oxidation in rat skeletal muscle (Sugimoto et al, 2008), improvement of glucose levels in CohenRosenthal hypertensive nonobese diabetic rats (Younis et al, 2010), and protection against diabetic complications in a mouse model (Toyama et al, 2011).…”
Section: A Peroxisome Proliferator-activated Receptorsmentioning
confidence: 99%
“…In contrast, six hours a er telmisartan exposure, the maximum levels of eNOS protein phosphorylation at Ser 1177 were observed, whereas r 495 phosphorylation at Ser 1177 diminished and phosphorylation at the inactivating r 495 residue increased; both changes were statistically signi cant. e telmisartan activity through PPARγ pathway has been reported widely in several models, tissues and conditions [24][25][26][27], as well as the stimulation of eNOS by telmisartan through a PPARγ and Rho-kinase pathway [28,29]. As is known, adipocyte di erentiation activates the transcription factor CCAAT/enhancer-binding protein β (C/EBPβ) [30], which subsequently stimulates PPARγ expression, insulin or insulin-like growth factor-1, promoting adipocyte di erentiation.…”
Section: Discussionmentioning
confidence: 99%